2013
DOI: 10.1128/aem.00279-13
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the panE Gene in Lactococcus lactis Enhances Formation of Cheese Aroma Compounds

Abstract: bHydroxyacid dehydrogenases limit the conversion of ␣-keto acids into aroma compounds. Here we report that inactivation of the panE gene, encoding the ␣-hydroxyacid dehydrogenase activity in Lactococcus lactis, enhanced the formation of 3-methylbutanal and 3-methylbutanol. L. lactis IFPL953⌬panE was an efficient strain producing volatile compounds related to cheese aroma. Flavor formation in dairy products is directly related to lactic acid bacteria (LAB), which are equipped with a large number of key intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Overall, the lack of the α-hydroxyacid dehydrogenase (HA-DH or PanE) activity did not change the L. lactis IFPL953 growth profile under BCAA starvation conditions. Similar growth behaviour was previously observed when both strains were grown in milk (Gómez de Cadiñanos et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Overall, the lack of the α-hydroxyacid dehydrogenase (HA-DH or PanE) activity did not change the L. lactis IFPL953 growth profile under BCAA starvation conditions. Similar growth behaviour was previously observed when both strains were grown in milk (Gómez de Cadiñanos et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…2). The inactivation of the panE gene, which limits the formation of α-hydroxy acids (Gómez de Cadiñanos et al, 2013), was related with higher expression of the kivD and ytjE genes and decreased expression of araT and bcaT (Fig. 2).…”
Section: Effect Of Bcaa Content and Pane Inactivation In The Relative Expression Of L Lactis Genes Involved In Amino Acid Catabolismmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been revealed that HICA can increase weight and muscle mass in chickens and rats (Boebel and Baker, 1982 ). In the present study, genes encoding enzyme 3-hydroxyisobutyrate dehydrogenase for conversion of 3HBA to acetoacetic acid and L-2-hydroxyisocaproate dehydrogenase (HicDH) for HICA production (de Cadiñanos de et al, 2013 ) were found in our probiotic genome (Table 2 ). However, functions of these metabolites in fish are not yet fully understood.…”
Section: Discussionmentioning
confidence: 60%